Location determinants of FDI: confronting theoretical approaches with empirical findings - Assunção, Susana; Forte, Rosa; Teixeira, Aurora A. C. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
The increase of foreign direct investment (FDI) in recent decades has prompted a great deal of research into the phenomenon of multinational companies. A vast amount of empirical literature on FDI presents a long list of determinants that try to explain direct investment by multinational companies in a particular location, such as infrastructure, market size, human capital, openness of the economy, and political stability. It is noticeable, however, that the results are not always consistent. This article provides a review of the theoretical approaches to, and empirical studies on, FDI in an attempt to single out the most robust factors for explaining the geographic distribution of FDI flows worldwide. It also suggests paths for future research in this area
Argumenta Oeconomica, 2013, Nr 2 (31), s. 5-28
Keywords: FDI; determinants of FDI; geographic distribution of FDI; multinational companies; literature review; inwestycje bezpośrednie; inwestycje zagraniczne; przedsiębiorstwo międzynarodowe